(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
Is hardly day expire without hearing the news either Abuse Managementthe accounting standards or the existence of serious misstatements by someauditors.Which caused the demanding of many companies in the recent republication of the financial statements and the re-announcement of its financialresults. Such acts raise questioning about the role that should be played by theauditors, prompting agencies responsible for setting auditing standards to takeTo throw increasingly responsibility on the auditors in order to interest risksfraud The Risks of Fraud in their review of the financial statements.also The Public Company Accounting Oversight Board in the U.S.called about the need of owning the Certified Public Accountants those whoaudits for powerful skills in the field of Certified fraud examination, but theserequirements raises a new question, namely! From Where we will bring thoseauditors who have the skills of fraud examination ،This research on the amodel application to the work of the legal examiner in the Office of the FederalFinancial Supervisory being the supreme audit functions of the fight againstfraud and corruption institution to maintain the misuse of public money andwaste disposal was built.